(untitled) (Veterinary Science, 2023)
This work aims to raise awareness about the harm caused by plastics dumped in the sea and provide information about the medical management of Pacific green turtle specimens under human care when they require attention. A case is presented of an adult female specimen of Chelonia mydas rescued in the city of Constitución, Chile, 200 km southwest of the Wildlife Rehabilitation Center (CRFS) at Parque Safari. The specimen shows symptoms of impaction syndrome with caudal flotation due to the accumulation of gases characteristic of paralytic ileus, and it also has lacerative injuries on the left anterior limb fin. It was decided to follow a diagnostic route with a clinical examination and complementary methods such as X-rays, ultrasounds, and blood analysis, in addition to a surgical procedure to expedite wound recovery. After three months of rehabilitation, the specimen was successfully reintroduced into Chascos Bay, Caldera, located 800 km north of the CRFS. During the rehabilitation of this specimen, it traveled approximately 1000 km across Chile’s routes from its rescue to its reintroduction, with contributions from both the public and private sectors to manage the process.